Mindfulness training for reducing anger, anxiety, and depression in fibromyalgia patients - Amutio, Alberto; Franco, Clemente; Pérez-Fuentes, María de Carmen; Gázquez, José J.; Mercader, Isabel (Frontiers in Psychology, 2015)
Fibromyalgia is a disabling syndrome. Results obtained with different therapies are very limited to date. The goal of this study was to verify whether the application of a mindfulness-based training program was effective in modifying anger, anxiety, and depression levels in a group of women diagnosed with fibromyalgia. This study is an experimental trial that employed a waiting list control group. Measures were taken at three different times: pre-test, post-test, and follow-up. The statistical analyses revealed a significant reduction of anger (trait) levels, internal expression of anger, state anxiety, and depression in the experimental group as compared to the control group, as well as a significant increase in internal control of anger. It can be concluded that the mindfulness-based treatment was effective after seven weeks. These results were maintained three months after the end of the intervention.